Examen especial a la cuenta de activos fijos de la cooperativa de transporte mixto "RÍO ZAMORA" de la ciudad y provincia de Zamora Chinchipe, en el período 2014 - Delgado Jaramillo, Dayhanna Nataly (2016)
The research titled "REVIEW SPECIAL ACCOUNT FIXED ASSETS OF TRANSPORTATION JOINT COOPERATIVE "ZAMORA RIVER "of the city and province of Zamora Chinchipe, IN THE PERIOD 2014" work done as a prerequisite for certification of engineer in Accounting and Audit, in order to assess whether the accounting for this account has been adequate, and thus be able to identify whether it has made proper use of fixed assets, thus allowing the real value be contrasted with the registered the books. And also through the research will be fulfilled with the aim of the special examination is to review the way in which asset records in the period January to December 2014 were made for it is attended the Cooperative and identified the other fixed assets for rear shape perform preliminary and specific planning for a second phase making the implementation of the special examination, performing internal control of fixed assets and thus to analyze the risk to continue working in this manner, the results of the special final examination report was prepared. Among the conclusions reached it is that there is inadequate enforcement of laws and regulations governing registration activities, depreciation and monitoring of fixed assets, so it is recommended to strengthen internal control of the Cooperative Truck "Zamora river" through the constant depreciation of fixed assets.